Fictitious proper names in Polish phraseology - Piela, Agnieszka (Papers in Linguistics, 2024)
Representing research in phraseology and onomastics, the article is devoted to fixed phrases featuring a fictitious proper name as a lexical component. The undertaken analysis encompasses historical and modern Polish phraseologisms with an etymologically reinterpreted fictitious onomastic component based on a witty or humorous play on words which uses various semantic and sound-related associations. It turns out that the distinctive feature of the discussed phraseologisms is their impermanence, for most of the historical lexical units are no longer used in the modern language. Only a few of such lexical combinations have survived until today, e.g. na święty Nigdy, pani Piasecka, pan Łopaciński, pojechać do Rygi. The article indicates the reasons for the lexical absence of the presented phraseological combinations (e.g. the jocular overtones or the growing obsolescence of vocabulary items).